STAKEHOLDER MARKETING DEFICIENCY: A PRACTICAL SYNTHESIS ON ETHICAL ISSUE DURING INDONESIAN BANKING INDUSTRY AGENCY ERA - Manaf, Peri A.; Suryadi, Silvya (Journal of Business Strategy and Execution, 2018)
The design of marketing strategy starts with a broad assessment of functional and psychosocial of stakeholder’s needs. Yet, recent realities are urging companies to consider beyond customers as the sole target of marketing activities and firms as the primary intended beneficiary. In the time of crisis, often managements were challenged with ethical decision which will affect its multiple stakeholders. When someone is challenged with an ethical dilemma, it leads to the deontological and teleological valuations of numerous courses of action resulting in ethical judgments. The purpose of this paper is to identify the related direct and indirect stakeholder’s influence to release and discharge letter from IBRA to BDNI and how it effects on the marketing stakeholders of the industry cluster. Using thematic analysis, we identify the related direct and indirect stakeholder’s influence to release and discharge letter from IBRA to BDNI and how it effects on the stakeholder marketing of the industry cluster.